ANALISIS PENGARUH BIAYA KONSTRUKSI TERHADAP PROFITABILITAS PT TURANGGA PUTRA TIMIKA - Diah Anggrany Savitry; Nely Salupadang (JURNAL ULET (Utility, Earning and Tax), 2019)
This study aims to determine the effect of construction costs on profitability ratios of (Gross Profit Margin) of PT Turangga Putra Timika. The researcher used the associative approach method which aims to determine the effect of material costs and construction costs on the profitability of the company. The instrument of data collection is documentation in the form of the 2013-2015 income statement prepared per quarter. Data analysis instruments use profitability ratios namely Gross Profit Margin and multiple linear regression analysis. The results show that material costs have a significant negative effect on profitability (Gross Profit Margin) while labor costs have a significant positive effect on profitability (Gross Profit Margin).